Perinatal features of the RASopathies: Noonan syndrome, Cardiofaciocutaneous syndrome and Costello syndrome. Issue 11 (22nd September 2014) - Myers, Angela; Bernstein, Jonathan A.; Brennan, Marie‐Luise; Curry, Cynthia; Esplin, Edward D.; Fisher, Jamie; Homeyer, Margaret; Manning, Melanie A.; Muller, Eric A.; Niemi, Anna‐Kaisa; Seaver, Laurie H.; Hintz, Susan R.; et al.
<x xml:space="preserve">Abstract</x> The RASopathies are a family of developmental disorders caused by heritable defects of the RAS/MAPK signaling pathway. While the postnatal presentation of this group of disorders is well known, the prenatal and neonatal findings are less widely recognized. We report on the perinatal presentation of 10 patients with Noonan syndrome (NS), nine with Cardiofaciocutaneous syndrome (CFCS) and three with Costello syndrome (CS), in conjunction with the results of a comprehensive literature review. The majority of perinatal findings in NS, CS, and CFCS are shared: polyhydramnios; prematurity; lymphatic dysplasia; macrosomia; relative macrocephaly; respiratory distress; hypotonia, as well as cardiac and renal anomalies. In contrast, fetal arrhythmia and neonatal hypoglycemia are relatively specific to CS. NS, CS, and CFCS should all be considered as a possible diagnosis in pregnancies with a normal karyotype and ultrasound findings of a RASopathy. Recognition of the common perinatal findings of these disorders should facilitate both their prenatal and neonatal diagnosis. © 2014 Wiley Periodicals, Inc.